1991
DOI: 10.1007/bf00011803
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of seedling root growth by coal-derived sodium humate

Abstract: Coal-derived sodium humate was found to stimulate primary root growth of seedlings of cantaloupe (Cucumis melo L.) at 1000mg L -1, lettuce (Lactuca sativa L.) and onion (Allium cepa L.) at 500 and 1000 mg L 1, as well as hypocotyl growth of cantaloupe at 1000 mg L-~. Growth enhancement was not due to release of nutrient elements by the product, and, in the case of lettuce and onion, was not due to increased availability or uptake of mineral elements. Growth stimulation of cantaloupe, however, was dependent on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Briefly, Na + humate is a humic acid salt obtained by sodium hydroxide extraction of black or brown coal (lignite or leonardite) and is used as a soil conditioner, as a stabilizer for ion exchange resins in water treatment, as a drilling additive in the drilling of wells for hydrocarbon exploration/extraction and geothermal drilling, and in the remediation of polluted environments (http://www.ahmadsaeed.com/sodium_Humate.html). Apart from its mainly industrial use, limited studies have also tested its effects on plant growth, with results ranging from none to stimulatory or negative effects (Van De Venter et al ., ; Sharif et al ., ; Iakimenko, ; Tahir et al ., ). However, the current use of Na + humate described here has not, to our knowledge, been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, Na + humate is a humic acid salt obtained by sodium hydroxide extraction of black or brown coal (lignite or leonardite) and is used as a soil conditioner, as a stabilizer for ion exchange resins in water treatment, as a drilling additive in the drilling of wells for hydrocarbon exploration/extraction and geothermal drilling, and in the remediation of polluted environments (http://www.ahmadsaeed.com/sodium_Humate.html). Apart from its mainly industrial use, limited studies have also tested its effects on plant growth, with results ranging from none to stimulatory or negative effects (Van De Venter et al ., ; Sharif et al ., ; Iakimenko, ; Tahir et al ., ). However, the current use of Na + humate described here has not, to our knowledge, been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In Van de Venter et al (1991) , coal -derived sodium humate was found to stimulate primary root growth of seedlings of cantaloupe ( Cucumis melo L.), lettuce ( Lactuca sativa L.), and onion ( Allium cepa L.). Growth enhancement was not due to the release of nutrient elements by the product; and, in the case of lettuce and onion, it was not due to increased availability or uptake of mineral elements.…”
Section: Morphological Changes In Response To Humic Substancesmentioning
confidence: 99%
“…Although results of studies of HA effects on plant growth are sometimes contradictory, some commonalities exist. These include the quadratic nature of plant responses, be it direct or indirect, to increasing amounts of HA (Lee and Bartlett 1976;Albuzio et al 1986;Van de Venter et al 1991).…”
mentioning
confidence: 99%